The Effect Of Prophylactic Intravenous Ephedrine On Lactic Acid Level Of Neonate During Spinal Anesthesia For Caesarean Section (Annals of Medical Research, 2021)
None
Keywords: s : Spinai anaesthesia, hypotension, ephedrine, lactic acid level.